2000
DOI: 10.4049/jimmunol.164.10.5287
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Alternative Splicing of CD45 by Antagonistic Effects of SR Protein Splicing Factors

Abstract: CD45 is a transmembrane glycoprotein possessing tyrosine phosphatase activity, which is involved in cell signaling. CD45 is expressed on the surface of most leukocytes and can be alternatively spliced by the inclusion or skipping of three variable exons (4, 5, and 6 or A, B, and C) to produce up to eight isoforms. In T cells, the splicing pattern of CD45 isoforms changes after activation; naive cells express high m.w. isoforms of CD45 which predominantly express exon A (CD45RA), whereas activated cells lose ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…Employing these two experimental approaches we concluded that the inhibition of CD45 splicing by cAMP-elevating agents was only slightly affected by the actions of these two cytokines and, therefore, other unknown mechanisms may be implicated in preventing CD45RO expression in cAMP-activated cells. It will be of interest to study the role of dbcAMP in regulation of the different proteins of the SR family of splicing factors that has been recently implicated in the alternative splicing of CD45 Ag, leading to either exon inclusion or skipping (3,33).…”
Section: Discussionmentioning
confidence: 99%
“…Employing these two experimental approaches we concluded that the inhibition of CD45 splicing by cAMP-elevating agents was only slightly affected by the actions of these two cytokines and, therefore, other unknown mechanisms may be implicated in preventing CD45RO expression in cAMP-activated cells. It will be of interest to study the role of dbcAMP in regulation of the different proteins of the SR family of splicing factors that has been recently implicated in the alternative splicing of CD45 Ag, leading to either exon inclusion or skipping (3,33).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that these SR proteins enhanced the Cµ4-M1 splice reaction relative to cleavagepolyadenylation at the µs poly(A) site. Although some coexpressed SR proteins have been shown to dramatically shift the RNA-splicing patterns of specific substrates in vivo (Caceres et al 1994;Du et al 1997;Bai et al 1999;ten Dam et al 2000), a twofold change in splice ratios has also been reported with other splice substrates (Caceres et al 1994;Screaton et al 1995;Jiang et al 1998;Bai et al 1999). There was no significant change in µ processing with coexpressed SRp40 and SC35 in either cell line (Fig.…”
Section: Splicing Environment Changes Affect µ Rna Processingmentioning
confidence: 99%
“…1B,C). SRp20 has been identified to be a part of a cleavagepolyadenylation enhancer complex (Lou et al 1998), but it also often affects alternatively spliced substrates differently than other SR proteins (e.g., Screaton et al 1995;ten Dam et al 2000). Thus, in the µ pre-mRNA, it is not clear whether SRp20 is enhancing cleavage-polyadenylation or repressing splicing.…”
Section: Splicing Environment Changes Affect µ Rna Processingmentioning
confidence: 99%
“…These proteins are specifically required for cross-exon interactions in both constitutively and alternatively spliced pre-mRNA. Recently, it was shown that relative levels of several SR proteins change upon T cell activation, inducing change in the pattern of CD45 pre-mRNA splicing (11). As other SR proteins, SRp40 recognizes specific 5 to 7 nucleotide-degenerated consensus sequence named exonic splicing enhancers, and at least 29 SRp40-specific exonic splicing enhancers have already been described (12).…”
mentioning
confidence: 99%